Estudio del sistema de ventilación para el control de agentes químicos y físicos, U.O. Pallancata – veta Pablo – 2018 - Llacho Alhuirca, Ubaldo Cesar (2020)
The present work is referred to the “Study of the ventilation system for the control of chemical and physical agents, U.O. Pallancata - Pablo vein - 2018”. It was carried out in order to study the efficiency and compliance with regulations regarding the distribution of air in the mine for the elimination of agents produced by blasting, hauling ore and transport. Data were taken on the concentrations of nitrous gases, carbon monoxide, carbon dioxide, oxygen, dust, temperatures and air velocity. These data were collected at different levels of exploitation of the Pablo vein. In conclusion, the current vein circuit Pablo does not manage to reach the air requirement for the elimination and control of the agents produced by mining extraction, likewise the change of circuit in veto Pablo is mentioned, with the culmination of RC 04 Pablo that would reach 102% coverage.